THE CORRELATION BETWEEN ENGLISH CLUB PARTICIPATION AND STUDEN’S' ENGLISH LEARNING ACHIEVEMENT AT SMAN 1 BARRU - Nawir, Aulia Ramanda; Nappu, Syamsiarna; Hambali, Uyunnasirah (Journal of Language Testing and Assessment, 2024)
This study aims to determine the correlation between students’ participation in the English Club Extracurriculars and their learning achievement. This research is a quantitative research with correlation method. The population of this study was students of class X MIPA SMAN 1 Barru with a sample of class X MIPA 1 who are selected by using purposive samplingtechnique for selecting the sample because the targetsample taken was students who took part in the English Club. The research data was coelected using two instruments; questionnaires and data documentation. The questionnaire used is an open-closed questionnaire with The document used is student learning outcomes. The questionnaire was distributed to the students who joined on English Club. Then the results was analyszed by calculating using the Spearman correlation analysis method using SPSS software with a significance level, the authors get a significant correlation of 0.008. The result is 0.008 < 0.05. Because 0.008 is lower than 0.005 (0.008 < 0.05), it means that there is a correlation between the student's participation in tutoring and the student's English achievement variable. In addition, from the data analysis, it was found that the Pearson Correlation was 0.621, which means that the correlation is strong according to the interpretation table correlation. Based on the research results, the null hypothesis is rejected. This means that there is a significant correlation between student participation in English Club and student learning achievements.